A critique of liberalism in contemporary French political thought Edgar Morin and Alain de Benoist are a model - mosaher, Waleed (Tikrit Journal For Political Science, 2024)
Since its inception, liberalism has been founded on freedom, individualism, and rationality in expanding its concept as an intellectual organization that attempts to advance the individual and his rights and help consolidate his position at the expense of society and not limit his freedom. The state must guarantee what it alone cannot guarantee for itself, which is security and protection. However, despite these foundations It gave freedom and rights to the individual, but it deprived the majority of them and did not guarantee equality between them, in addition to transforming these principles from a national policy into an international propaganda policy and a cover for interfering in the affairs of countries and imposing their culture and values on them, which led to a lack of dialogue between peoples due to differences in cultures, and forced people to Living in selfishness, alienation and other crises that require radical reforms were led by Edgar Morin and Alain de Benoist, who provided a critical vision for it